2015
DOI: 10.1088/0031-9155/60/20/7927
|View full text |Cite
|
Sign up to set email alerts
|

A method to correct for temperature dependence and measure simultaneously dose and temperature using a plastic scintillation detector

Abstract: Plastic scintillation detectors (PSDs) work well for radiation dosimetry. However, they show some temperature dependence, and a priori knowledge of the temperature surrounding the PSD is required to correct for this dependence. We present a novel approach to correct PSD response values for temperature changes instantaneously and without the need for prior knowledge of the temperature value. In addition to rendering the detector temperature-independent, this approach allows for actual temperature measurement us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Furthermore, online self -correcting technology for temperature dependence of detector probes has been developed for a detector system using multipoint plastic scintillators. 39 Developing a similar self -correcting algorithm for ZnSe:O could be considered, as ZnSe:O displays a large temperature dependence. However, manual correction for the difference between calibration and patient temperatures is still feasible.…”
Section: Temperature Dependence Of the Znse:o Crystal's Responsementioning
confidence: 99%
“…Furthermore, online self -correcting technology for temperature dependence of detector probes has been developed for a detector system using multipoint plastic scintillators. 39 Developing a similar self -correcting algorithm for ZnSe:O could be considered, as ZnSe:O displays a large temperature dependence. However, manual correction for the difference between calibration and patient temperatures is still feasible.…”
Section: Temperature Dependence Of the Znse:o Crystal's Responsementioning
confidence: 99%
“…One such detector, the plastic scintillation detector (PSD), has several advantages that have been recently highlighted in the literature, a key one being their real-time response. [7][8][9][10][11][12][13][14][15][16][17] Although PSDs are affected by the stem effect and temperature variations, 12,13 several investigations have developed methods to correct both of these dependencies in the detector response. 7,9,14,15,[18][19][20][21] Most of the studies characterizing PSD response were conducted using an optical fiber connected to a single point of measurement as a sensitive volume.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Tanderup et al highlighted the main aspects of various detectors that could be used as in vivo dosimeters in brachytherapy. One such detector, the plastic scintillation detector (PSD), has several advantages that have been recently highlighted in the literature, a key one being their real‐time response . Although PSDs are affected by the stem effect and temperature variations, several investigations have developed methods to correct both of these dependencies in the detector response …”
Section: Introductionmentioning
confidence: 99%
“…Plastic scintillator detectors (PSDs) show promise for obtaining accurate real‐time radiotherapy dose measurements. Previous studies have demonstrated that PSDs can accurately measure dose in external beam radiotherapy and that they have high spatial resolution, linearity with dose, energy independence in the megavolt energy range, and water equivalence . In addition, some authors have found PSDs to be feasible for use in brachytherapy applications .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that PSDs can accurately measure dose in external beam radiotherapy and that they have high spatial resolution, linearity with dose, energy independence in the megavolt energy range, and water equivalence. [3][4][5][6][7][8][9][10][11][12] In addition, some authors have found PSDs to be feasible for use in brachytherapy applications. [13][14][15][16][17] Despite the aforementioned advantages, PSD response is affected by the stem effect and temperature dependence.…”
Section: Introductionmentioning
confidence: 99%